Study on the Viable but Non-culturable (VBNC) State Formation of Staphylococcus aureus and Its Control in Food System - Li, Yanmei; Huang, Teng-Yi; Mao, Yuzhu; Chen, Yanni; Shi, Fan; Peng, Ruixin; Chen, Jinxuan; Yuan, Lei; Bai, Caiying; Chen, Ling; Wang, Kan; Liu, Junyan (Frontiers in Microbiology, 2020)
Viable but nonculturable (VBNC) state, a bacterial survival strategy under reverse conditions, poses significant challenge for public health and food safety. In this study, the effect of the external environmental conditions including acid, nutrition and salt concentrations on the formation of S. aureus VBNC state at low temperature were investigated. Different acidity and nutritional conditions were then applied on food products to control the VBNC state formation. Four different concentration levels of each factors (acid, nutrition and salt) were selected in the total of 16 experimental groups. Nutrition showed the highest influence on the VBNC state formation S. aureus, followed by acid and salt. The addition of 1% acetic acid could directly kill S. aureus cells and inhibit the formation of VBNC state with nutrition concentration of 25%, 50% and 100%. And propidium monoazide-polymerase chain reaction (PMA-PCR) assay was applied and considered as a rapid and sensitive method to detect S. aureus in VBNC state with the detection limit of 104 CFU/mL.